Pelatihan Profesional, Penghargaan Finansial dan Pertimbangan Pasar Kerja: Minat Berkarir Akuntan Publik - Sugihartanto, Elizabeth Angelina Noer; Purwantoro, Purwantoro; Mardjono, Enny Susilowati; Minarso, Bambang (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
This study examines the influence of professional training, financial rewards, and job market factors on public accountant career interests. The study employed a quantitative method, utilizing primary data sources, by distributing questionnaires to Accounting students at Dian Nuswantoro University, Semarang. The sample consisted of 53 respondents. The data was analyzed using multiple linear regression, using SPSS 25 for processing. The study indicates that professional training and job market factors significantly influence interests in a public accountant career, while financial rewards do not influence public accountant career interest. This study suggests that students can enhance their understanding of the public accounting profession, companies can consider accounting graduates, and KAP (Public Accounting Firm) can be used as a recommendation for selecting accountants.